Relationship Between Strategic Planning and Organizational Performance: Case of Moroccan Organizations - BELAFHAILI Mohamed, M.; Nafzaoui, Achraf; SEBBAR, Abdellah; BERDI, Abdelaziz (International Journal of Engineering and Technology, 2019)
Strategic planning has become a fashionable theme in recent years, often used to legitimize the formalization efforts of the management concept in organizations. This is a central theme in organizational theory, but it remains hard to access. The purpose of this article is threefold. It first presents a state of knowledge on the subject of this basis. It then proposes a model referring to the main steps for strategic formalization. And finally, it allows us to situate the relationship between strategic planning and performance in Moroccan organizations. These theoretical contributions are increasingly being used to analyze the contribution of strategy in improving the performance of organizations as Winston Churchill said: â€œLet the strategy be beautiful is a fact, but do not forget to look at the resultâ€.Â Â